Effect of isolated mesophilic bacterial consortium on pressed-shredded empty fruit bunch composting process - Lai, Jia; Chua, Han; Saptoro, Agus; Ang, Ming (School of Engineering & Information Technology, Universiti Malaysia Sabahh, 2012)
Empty fruit bunch (EFB) is one of the main solid wastes generated from palm-oil mills.Incineration and mulching have been employed traditionally to process EFB. This methodof waste treatment becomes a great concern since burning of EFB is prohibited byregulation and moreover, the process is costly and unsustainable. Composting of EFB hasthe potential to replace the conventional methods used. Composting is a bioconversionprocess involving microbial activity that transforms biomass wastes into useful organicsubstrate or fertilizer. In this work, an experimental study was carried out to investigate thesimple composting of pressed-shredded empty fruit bunch (EFB) with mesophilic bacterialconsortium as composting microorganism. The bacterial consortium was isolated fromempty fruit bunch compost and cultivated under mesophilic condition at 35 oC. Theexperiment was conducted under ambient condition and the process was carried out forduration of 40 days. Changes in physicochemical characteristics of composting process wasrecorded and evaluated. The composting was performed at a temperature range of 26.5-28 oC. The pH was found to increase from pH 6.51 to average pH 9.82 after 5 days ofcomposting process and moisture content fluctuated between 60% to 80% over the periodof study. An average of 54% reduction of EFB dry weight was achieved using the isolatedmesophilic bacterial consortium following the composting process.